Uma genealogia do ensino de química no Brasil - Rigue, Fernanda Monteiro (2017)
The present dissertation aims investigate the competing forces for the appearance of Chemistry as a compulsory discipline for every Brazilian youth. Through a Genealogical panorama (FOUCAULT, 1979), we seek present the set of forces committed to establishing this science as a discipline in Brazil, as well as its first manifestations, in order to identify and understand the conditions of possibility that made it emerging in the curriculum as a Teaching of Chemistry for every Brazilian youth. Starting with the three blocks that base the dissertation, which per pass through the Teaching of Chemistry in Brazil of the Colonial and Imperial Period - meeting the Pombaline Reform and the Statutes of Coimbra University, passing through the First Republic and Brazilian developmentalism, the first and second major world wars, venturing to question the Sputnik satellites 1 and 2, the Military Dictatorship in Brazil and the MEC / USAID agreements. Rare are the authors who have studied the establishment of Chemistry Teaching in Brazil, however, without aiming to understand the state operations and forces that contributed to consolidation of a single curriculum, contemplating this discipline in the country. The "said" and "unsaid", much less than telling 'a' History of Teaching Chemistry in Brazil, seek, through this work of dissertation, think individualization by way of totalization in the National School, strongly related to Theory of Systems. We seek to problematize, from a Genealogical perspective, what we are doing with what they have done for us during this movement of establishing and consolidating the compulsory teaching of Chemistry for 'everyone' and 'each one'. Map to open other spaces, movements, and look carefully for the emergence of the Training of Chemistry Teachers in this context. The present dissertation covers the Education History in Brazil, the Science History and state operations during interest developmental, up to LDBEN No. 5,692 of 1971, at the height of the Military Dictatorship.